STRATEGI KOMUNIKASI BADAN KENAZIRAN MASJID AL BUCHARI KELURAHAN GEDUNG JOHOR DALAM MENARIK MINAT JEMAAH MENGIKUTI PENGAJIAN AHAD PAGI - Farid Arkana Silalahi; Muaz Tanjung (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study aims to determine the communication strategy of the Kenaziran Board of Masjid Al Buchari Kelurahan Gedung Johor in attracting congregations to attend Sunday morning recitation. This research is qualitative research with a descriptive method. This research is a field study (field research). Data sources in this study include primary data obtained directly through phenomena in the research arena and secondary data obtained indirectly through relevant literature. Data collection techniques in this study include interviews, observation, and documentation. Data analysis techniques in this study include data reduction, data presentation, and conclusions. This study's results indicate that effective communication based on understanding and empathy for the needs of the communicant has a very important role in attracting congregations to attend Sunday morning recitations. Al Buchari Mosque's Kenaziran Board uses various communication strategies, such as personal communication, mosques and social media announcements, and involving the congregation in planning and organizing recitations. They are also selective in selecting competent and well-known speakers and try to build positive relationships with the community through social activities. However, several obstacles are encountered, such as long holidays, other events close to the mosque, and the congregation's busyness, which can affect their participation in the Sunday morning recitation.